The characteristics of Jews and Christians in the Qur'an : a study of selected tafasir - Islam, Mohammad Aminul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research seeks to identify the characteristics of Jews and Christians based on the verses of the Holy Qur'an. The study found that some of those verses indicate that the Christians believe in Allah s.w.t and what has been revealed to Prophet Muhammad (peace be upon him) and to their Prophet Isa (peace be upon him). Other verses show that they do not believe in Allah as He wants, and what He revealed to Prophet Muhammad (peace be upon him). This thesis acknowledges that some verses say Allah granted to the Jews what He had not granted to anyone else in the world, He Himself says, He has chosen as the best Ummah (people) the Ummah of Prophet MuÍammad (peace be upon him). Sometimes it seems to the readers of the Qur'an that the Christians and the Jews are the same and sometimes it is like Christians are closer to Muslims than the Jews. Moreover, the Christians seem to be better than the Muslims to readers of the Qur'an sometimes. Hence, there appear some contradictions in the Qur'anic verses, which might lead the readers to confusion over the Holy Qur'an. In conjunction, this paper aims to clarify the contradictions among the Qur'anic verses regarding Jewish and Christian characteristics using descriptive and analytical methods. This research is firmly to be just to those who have good characteristics to testify them as good and who are not good, to testify them as not good according to the Qur'anic verses. On top of that, this research contributes to building a peaceful religious co-existence among multi-religious societies. The most significant finding of this research is that there is no conflict within the Qur'anic verses concerning the characteristics of Jews and Christians. However, what appear here, as conflicts and contradictions among Qur'anic verses, are merely literal. Not all Jews and Christians have bad characteristics; rather, according to the Qur'an, there are some Jews and Christians who have good manners. The findings of the paper will tremendously fulfill its objectives and contribute to generating a peaceful religious co-existence among Muslims, Jews and Christians.